(untitled) (Scientific journal of the Fergana State University, 2025)
This paper presents the results of the extraction of terpenoids found in plants such as lavender, rosemary and mountain basil, which are some members of the family Labiatae (lamiacae), and their determination using qualitative reactions and GC-MS methods. The results revealed the presence of eucalyptol (1,8-cineole), linalool, bornanone, endoborneol, linyl acetate, endoborneol, beta-pinene, camphor, terpinen-4-ol, caryophyllene, alpha-terpineol and other compounds. at the factory. Along with this, the article provides a complete analysis of the results obtained.